Cognitive performance was reduced by higher air temperature even when thermal comfort was maintained over the 24–28°C range - Lan, Li; Tang, Jieyu; Wargocki, Pawel; Wyon, David P; Lian, Zhiwei (Indoor Air, 2022)
This study managed to create thermal comfort conditions at three temperatures (24°C-T24, 26°C-T26, and 28°C-T28) by adjusting clothing and air velocity. Thirty- six subjects (18 males and 18 females) were exposed to each of the three conditions for 4.5 h in a design balanced for order of presentation of conditions. During each exposure, they rated the physical environment, their comfort, the intensity of acute subclinical health symptoms, and their mental load, and they performed a number of cognitive tasks. Their physiological reactions were monitored. The subjects rated T24 to be comfortably cool, T26 to be comfortably neutral, and T28 to be comfortably warm. Their self-estimated performance did not differ between conditions but 12 of 14 objective metrics of cognitive performance decreased significantly at the elevated temperatures: compared with T24, their average cognitive performance decreased by 10% at T26 and by 6% at T28. At the elevated temperatures, their parasympathetic nervous system activity (as indicated by PNN50) and their arterial blood oxygen saturation level (SpO2) were both lower, which would be expected to result in reduced cognitive performance. The subjects also rated their acute subclinical health symptoms as more intense and their workload as higher at the elevated temperatures. These results suggest that where cognitive performance is the priority, it is wise to ensure a comfortably cool environment. The present study also supports the use of fans or natural ventilation to reduce the need for mechanical cooling.
KerkoCite.ItemAlsoKnownAs: 10.1111/ina.12916 2129771:IZDK8FG8 4682641:CIQ8XNFD 4682641:M2MHIUAK 5072953:JG79T4UC openalex: W3184331866
Keywords: BE:RELEVANT; C:China; _z:class:countries; _z:class:themes; evidence_review; oa:keyword:cognitive performance; oa:keyword:higher air temperature; oa:keyword:thermal comfort; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T11109 Physiological Responses to Heat Stress in Humans; oa:topic:T11244 Impact of Climate Change on Human Health; openalex:n:1; openalex:yes

A survey of bedroom ventilation types and the subjective sleep quality associated with them in Danish housing - Liao, Chenxi; Akimoto, Mizuho; Bivolarova, Mariya Petrova; Sekhar, Chandra; Laverge, Jelle; Fan, Xiaojun; Lan, Li; Wargocki, Pawel (Science of The Total Environment, 2021)
We performed a survey of the types of bedroom ventilation in Danish dwellings (January–February 2020) and the associated subjective sleep quality. Five hundred and seventeen people responded. Their median age was 33 years old and 55.4% of them were males. We used an online questionnaire and collected information on the type of bedroom ventilation, bedroom airing behaviour by the respondents, the bedroom environment, building surroundings and location, and sleep disturbance caused by stuffy air, noise, and the thermal environment. Subjective sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI); its median among respondents was >5 indicating reduced sleep quality. 35.4% of the bedrooms had mechanical, 24.6% exhaust, and 40.0% natural ventilation. Sleeping in a bedroom with mechanical ventilation tended to reduce sleep disturbance. The absence of mechanical ventilation and the presence of carpet in the bedroom were all associated with stuffy air causing sleep disturbance, which was the second most sleep disturbing factor. PSQI increased significantly with increased sleep disturbance. People who reported that their sleep was disturbed by stuffy air or “too warm” conditions opened windows frequently during the day or night, but no association was found between PSQI and bedroom airing behaviours. Our results are valid for the heating season and the survey would have to be repeated in the non-heating season to permit generalization of the findings. The results present associations and are qualitative, so field measurements are necessary to validate the present observations and provide further explanations.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.scitotenv.2021.149209 2129771:5DU85DEJ 4682641:W4ZVX6EJ 5072953:S9TX6GQB openalex: W3186482159
Keywords: BE:RELEVANT; Noise; Occupant behaviour; PSQI; Sleep disturbance; Stuffy air; Thermal comfort; _z:class:countries; _z:class:themes; oa:keyword:bedroom ventilation types; oa:keyword:subjective sleep quality; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T10316 Sleep and Insomnia; oa:topic:T11692 Effects of Noise Pollution on Health and Well-being; openalex:n:1; openalex:yes